2017
DOI: 10.4081/or.2017.7063
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of continuous femoral nerve block with and without combined sciatic nerve block after total hip arthroplasty: a prospective randomized study

Abstract: In association with the growing interests in pain management, several modalities to control postoperative pain have been proposed and examined for the efficacy in the recent studies. Various modes of peripheral nerve block have been proposed and the effectiveness and safety have been examined for each of those techniques. We have described our clinical experiences, showing that continuous femoral nerve block could provide a satisfactory analgesic effect after total hip arthroplasty (THA) procedure. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…It is also imperative to consider robust pain control, albeit temporary, in the immediate post-operative period including the use of nerve blocks. 19 …”
Section: Discussionmentioning
confidence: 99%
“…It is also imperative to consider robust pain control, albeit temporary, in the immediate post-operative period including the use of nerve blocks. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, the xed effects model was used.Only a CI was provided in two studies [19][20] , the SD was calculated using the following formula where U refers to the upper limit of the CI, u to the mean, s to the SD and n to the number of study participants in each group. U-u=s/sqrt(n) 2 When P < 0.05 was considered signi cant. Sensitivity analysis was used to nd potential sources of signi cant heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Total hip arthroplasty (THA) is considered to be the most effective surgical treatment for patients with severe hip disease [1][2]. In spite of the satisfactory results of THA, because patients suffer blood loss during the perioperative period, surgery carries risks of postoperative anemia and blood transfusion, leading to longer hospital stays and higher medical costs [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…76 A study performed by Nishio et al has indicated that combination sciatic and femoral nerve block offers adequate analgesia, on the basis of reported pain scores at 6and 12-hour time points in patients undergoing THA. 77 Recent evidence has suggested that nerve block analgesia for patients after THA should be avoided in favor of systemic analgesia, owing to onset of low extremity weakness. 76 Specifically, in up to 90% of cases following femoral nerve block or quadratus lumborum block, there is onset of significant quadriceps weakness, in which case the adverse consequences of falling may significantly outweigh the benefit of analgesia.…”
Section: Epidural Catheters and Peripheral Nerve Blocksmentioning
confidence: 99%